2019
DOI: 10.4067/s0718-07642019000300237
|View full text |Cite
|
Sign up to set email alerts
|

Los Dominios de la Personalidad y su Relación con el Estilo de Liderazgo Transformacional

Abstract: ResumenSe evalúa el impacto de los dominios de la personalidad y la experiencia de trabajo en el estilo de liderazgo transformacional, entregando nuevas evidencias de la relación causal entre ambos constructos. La investigación tuvo un enfoque cuantitativo con un diseño de investigación no experimental, de corte transversal y de alcance correlacional-causal. Se realizó una encuesta a 368 profesionales que cursan programas de posgrado en Administración de Empresas en el Ecuador. El instrumento denominado Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…According to Arévalo-Avecillas et al ( 2019) the United States of America has produced most of the empirical studies tackling the relationship between personality and leadership, and although Norway, Australia, Singapore, and Canada have shown a few other set of studies on the correlation between these two constructs, no similar efforts are evident from developing countries (Arévalo-Avecillas et al, 2019). In a recent study, Zárate-Torres et al (2022) reported the scarcity of Latin-American studies focusing on the relationship between personality, gender, and leadership.…”
Section: The Impact Of Personality On Leadershipmentioning
confidence: 99%
“…According to Arévalo-Avecillas et al ( 2019) the United States of America has produced most of the empirical studies tackling the relationship between personality and leadership, and although Norway, Australia, Singapore, and Canada have shown a few other set of studies on the correlation between these two constructs, no similar efforts are evident from developing countries (Arévalo-Avecillas et al, 2019). In a recent study, Zárate-Torres et al (2022) reported the scarcity of Latin-American studies focusing on the relationship between personality, gender, and leadership.…”
Section: The Impact Of Personality On Leadershipmentioning
confidence: 99%